Kazimierz Twardowski jako wzór osobowy nauczyciela akademickiego - Zegzuła-Nowak, Joanna (Annales. Etyka w Życiu Gospodarczym, 2012)
The main aim of the article is a justification and attempt to prove the rightness of the thesis that personal features and teaching, educational and pedagogical activity of Kazimierz Twardowski constitute the example of teaching attitude which may be set as a personal model for modern team of academic teachers. The attitude of Kazimierz Twardowski proves that the work of a teacher treated as a life mission is a kind of social service contributing to development of culture and science. For the work of an academic teacher should be based on realizing of the values, ideals and attitudes socially desired, otherwise the society is threatened with not only stagnation or degradation of science but also arising and developing of attitudes which are socially harmful.